Novel ceramic Gd3M2Al3O12: M=Ce+3, Fe+3:Optical properties and potential applications - Dewasthali Tejaswi Ramchandra; Suman Rani (Chemical Physics Impact)
Garnets are becoming popular for improving photonic device efficiency due to their chemical and physical stability, making them ideal for electronics, optics, and material science. This work studies the structural and optical properties of Gd3Ce2Al3O12 (GCAG) and Gd3Fe2Al3O12 (GFAG), synthesized using the sol-gel method, with sintering at 1100 °C for GCAG and 950 °C for GFAG. FESEM and FTIR spectroscopy were used to analyze phase composition and microstructure. UV–Vis spectroscopy revealed a band gap of 3.73 eV for GCAG and 2.63 eV for GFAG. Both GCAG and GFAG exhibit multicolor emission in their Down Conversion (DC) emission spectra, highlighting their intriguing optical properties.